Effect of COVID-19 on childhood Mycoplasma pneumoniae infection in Chengdu, China - Zhang, Ying (BMC Pediatr, 2021)
BACKGROUND: Following the outbreak of the COVID-19 pandemic, a change in the incidence and transmission of respiratory pathogens was observed. Here, we retrospectively analyzed the impact of COVID-19 on the epidemiologic characteristics of Mycoplasma pneumoniae infection among children in Chengdu, one of the largest cities of western China. METHOD: M. pneumoniae infection was diagnosed in 33,345 pediatric patients with respiratory symptoms at the Chengdu Women’s & Children’s Central Hospital between January 2017 and December 2020, based on a serum antibody titer of ≥1:160 measured by the passive agglutination assay. Differences in infection rates were examined by sex, age, and temporal distribution. RESULTS: Two epidemic outbreaks occurred between October-December 2017 and April-December 2019, and two infection peaks were detected in the second and fourth quarters of 2017, 2018, and 2019. Due to the public health response to COVID-19, the number of positive M. pneumoniae cases significantly decreased in the second quarter of 2020. The number of M. pneumoniae infection among children aged 3–6 years was higher than that in other age groups. CONCLUSIONS: Preschool children are more susceptible to M. pneumoniae infection and close contact appears to be the predominant factor favoring pathogen transmission. The public health response to COVID-19 can effectively control the transmission of M. pneumoniae.